EDUKASI MENGENAI PENYAKIT ALZHEIMER PADA PENGUNJUNG POLI NEUROLOGI DI RSUD PROVINSI NUSA TENGGARA BARAT DAN RS UNIVERSITAS MATARAM - fitriantoro, santo; Harahap , Herpan Syafii; Landapa, Raditya Rachman; Suryani, Dini; Wardi, Baiq Prita Riantiani; Putri, Siti Noururrifqiyati Juna; Anjani, Dewa Ayu Vania Novista; Fakar, Wina Arsylia; Wulandari, Rizka; Mawaddah, Alfia; Rahma, Elrica Nadia; Novsyaini, Zhayyin Palna Rial (Universitas Mataram, 2024)
Alzheimer’s disease is the most common form of dementia, characterized by progressive cognitive decline, affecting memory, thinking abilities, and behavior. Education about Alzheimer’s disease is crucial to raise awareness regarding early symptoms, risk factors, and appropriate management, especially among neurology clinic visitors who are at high risk. This study aims to evaluate the effectiveness of education about Alzheimer’s disease among visitors of the neurology clinics at the Provincial General Hospital of West Nusa Tenggara and Mataram University Hospital. Educational sessions were conducted at two locations: the Provincial General Hospital of West Nusa Tenggara and Mataram University Hospital. The sessions included visual presentations and Q&A sessions. The effectiveness of the education was assessed by comparing pre-test and post-test scores, which measured participants’ understanding of Alzheimer’s disease. The average post-test score at Mataram University Hospital increased to 88 from a pre-test score of 76. At the Provincial General Hospital of West Nusa Tenggara, the average post-test score increased to 72.3 from a pre-test score of 67.69. This improvement indicates that the educational sessions effectively enhanced participants’ understanding of Alzheimer’s disease. Educational sessions using presentations effectively increased the understanding of neurology clinic visitors regarding Alzheimer’s disease. There is a need for broader dissemination of information at various healthcare facilities to improve public awareness and promote early detection and better management of Alzheimer’s disease.